Urgensi penerapan Analisis Dampak Lingkungan (AMDAL) dalam persyaratan perizinan usaha sebagai strategi pembangunan menuju keseimbangan ekologis di Indonesia: - - Mulia, Wine Antika (Maliki Interdisciplinary Journal, 2024)
All Indonesian citizens have the importance of always protecting and protecting the surrounding environment. This is mandatory in order to prevent an environmental crisis from occurring in this country. In response to this, Indonesia subsequently enacted the Law on the Management and Protection of the Living Environment. Therefore, efforts to support the implementation of a mandatory sustainable development policy need to be carried out analysis of the impact of development on the environment (AMDAL). AMDAL becomes a legal framework that will subsequently raise awareness of project managers activities so as not to damage the ecological system in Indonesia.